Acute Myeloid Leukemia in Infants: Biology and Treatment - Masetti, Riccardo; Vendemini, Francesca; Zama, Daniele; Biagi, Carlotta; Pession, Andrea; Locatelli, Franco (Frontiers in Pediatrics, 2015)
Children aged 0–2 years (i.e. infants) with acute myeloid leukemia (AML) are a peculiar subgroup of patients in the childhood AML scenario. They present with distinctive biological and clinical characteristics, including a high prevalence of prognostically unfavorable risk factors and an increased susceptibility to therapy-related toxicity. Remarkable improvements have been achieved over the last 2 decades in the treatment of these patients and their outcome is becoming superimposable to that of the older age groups. In this review, we will focus on peculiarities of this young subgroup of children with AML, describing their clinical presentation, the biology of disease and factors influencing outcome. Treatment results and toxicity data reported by major collaborative groups are also summarized and compared.